Pengaruh Rasio Likuiditas dan Rasio Rentabilitas Sub Sektor Perkebunan yang Terdaftar di Bursa Efek Indonesia Periode 2012-2016 - Revisya Indri Yanti; Hari Susanta Nugraha (Universitas Diponegoro, 2018)
This research had purpose to analyzed some of the fundamental factors of financial rations that could to be use as a signal for investors to predicted stock prices on companies in a sector thatis growth in Indonesia, which was plantantion sub-sector. Variabels that examined in this study were the Likuidity Ratio (consists of Current Ratio, Quick Ratio, Cash Ratio and Net working Capital) and Profitability Ratio (consists of Return on Assets and Return on Equity) on the stock price, eather partially or simultaneously on the plantation sub sector companies that have been listed in the Indonesia Stock Excahange in 2012-2016. This research wa an explanatory research with a total sample of 9 companies x 5 years = 45 observasiton data. The analysis technique used was multiple regression analysis and hypothesis testing using t test partial, F test simultaneously with the level of significance of 5% and a determination coefficient test. The Analysis showed the data have fulfilled classical assumption, including normally distributed data, no symptomps of multikolinearitas, there were no symptoms of autocorrelation and heteroscedaticity. The regression results Quick Ratio and Return On Equity were partially significant effeck on stock prices. While Current Ratio, Cash Ratio, Net working Capital and Return On Assets partially were not significant effeck on stock prices. Variabels used in this study (Likuidity Ratio and Profitability Ratio) simultaneously affeck the stock prices.